2009
DOI: 10.1080/13803390902971131
|View full text |Cite
|
Sign up to set email alerts
|

Impaired procedural learning in language impairment: Results from probabilistic categorization

Abstract: The Weather Prediction (WP) Task is a classical task of probabilistic category learning generally used for examining the dissociation of procedural and declarative memory. The current study focuses on performance of children with language impairment (LI) and compares their performance to that of typically developing (TD) children and adults with the aim of testing the procedural deficit hypothesis of LI (PDH; Ullman & Pierpont, 2005), which states that language impairment is not a specific linguistic phenomeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 44 publications
4
66
1
Order By: Relevance
“…These include differences in the nonverbal IQ test used, the nonverbal IQ cutoff score criterion for participant inclusion, participants' age, and whether the studies matched the SLI and TD groups for SES. On the basis of prior work demonstrating subtle nonverbal cognitive deficits in children with SLI (e.g., Archibald & Gathercole, 2006b;Kemény & Lukács, 2010; and a handful of studies suggesting that children with SLI obtain lower nonverbal IQ test scores than their TD peers (Cole et al, 1994;Miller & Gilbert, 2008), we expected that the children with SLI would score significantly lower than their TD peers on nonverbal IQ tests. Figure 1 provides a flow chart illustrating the selection of the final studies included in the meta-analysis.…”
Section: Purpose Of Present Studymentioning
confidence: 98%
See 3 more Smart Citations
“…These include differences in the nonverbal IQ test used, the nonverbal IQ cutoff score criterion for participant inclusion, participants' age, and whether the studies matched the SLI and TD groups for SES. On the basis of prior work demonstrating subtle nonverbal cognitive deficits in children with SLI (e.g., Archibald & Gathercole, 2006b;Kemény & Lukács, 2010; and a handful of studies suggesting that children with SLI obtain lower nonverbal IQ test scores than their TD peers (Cole et al, 1994;Miller & Gilbert, 2008), we expected that the children with SLI would score significantly lower than their TD peers on nonverbal IQ tests. Figure 1 provides a flow chart illustrating the selection of the final studies included in the meta-analysis.…”
Section: Purpose Of Present Studymentioning
confidence: 98%
“…In addition to deficits in language, a number of researchers have found that many children with SLI also present with subtle deficits in nonverbal cognition, including but not limited to auditory and visual attention (e.g., Finneran, Francis, & Leonard, 2009;Noterdaeme, Amorosa, Mildenberger, Sitter, & Minnow, 2001;, visuospatial working memory (e.g., Archibald & Gathercole, 2006b;Bavin, Wilson, Maruff, & Sleeman, 2005;Hick, Botting, & Conti-Ramsden, 2005), serial reaction time learning (e.g., Kemény & Lukács, 2010;Tomblin, Mainela-Arnold, & Zhang, 2007), and deductive reasoning (e.g., Newton, Roberts, & Donlan, 2010). In contrast to linguistic-based theories, which isolate the deficits of SLI to the linguistic system, cognitive-based theories attempt to account for both the linguistic and the nonlinguistic cognitive difficulties of children with SLI by positing that they both stem from a nonlinguistic cognitive or processing deficiency.…”
Section: Theoretical Accounts Of Slimentioning
confidence: 98%
See 2 more Smart Citations
“…Studies have shown that children (Kemeny & Lukacs, 2010;Lum, Gelgic, & Conti-Ramsden, 2010), adolescents (Tomblin, Mainela-Arnold, & Zhang, 2007), and adults (Lee & Tomblin, 2012) with DLI have more limited procedural memory ability for verbal information. Findings are less consistent with the PDH when the procedural memory task involves nonverbal information (Lum & Conti-Ramsden, 2013) or when the task does not involve learning discrete sequences (Hsu & Bishop, 2014).…”
Section: Processing and Linguistic Knowledge Differences In DLImentioning
confidence: 99%